(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To evaluate the knee society and functional score in pre-and post-operative patients of Total Knee Replacement. Method: A cross sectional, observational study comprising of 40 patients evaluated at 1 year follow up done by single surgeon in same setup from July 2015 to June 2016. Data taken from Pakistan national joint registry (PNJR). Knee society score evaluated pre-operative and post-operative at 1 year follow up. Result: In our study total of 40 patients were analyzed which comprises of 30% (n= 12) male and 70% (n= 28) female patient with age range of 40 to 70 years with mean age of 55.45 9.25 years. Out of 40, 90 % patients (n=36) had osteoarthritis and 10 % (n= 4) had rheumatoid arthritis. The average pre-operative knee society score is 51.07±13.3 and functional pre-operative score is 42.87 16.4 while post op knee society score is 91.75 3.44 and functional score post op is 87.32 6.33. Conclusion: Total Knee Replacement is the best modality for arthritis of knee as the scores in terms of knee society and functional score has improved.